When is better really better? Individuals' experiences of treatment for OAB with anticholinergic medication. Issue 1 (11th August 2016) - Kinsey, Debbie; Alexander, Tim; Glover, Lesley; Pretorius, Sara; Kraus, Sigurd; Duggan, Paul
ABSTRACT: Overactive bladder (OAB) has been found to have a number of psychological consequences, including anxiety, depression and shame. However, there is little research on how drug treatment, which has been found to be effective at reducing physical symptoms, impacts on these psychological effects. This study aimed to examine patients' experiences of anticholinergic treatment for OAB, and the impact of both OAB and its treatment on psychological well‐being. A cross‐sectional, qualitative interview design with a secondary care outpatient sample was used. The approach was idiographic and sought to understand the detailed complexities and nuances of patient experiences. This small‐scale qualitative study found that, even where there had been symptom reduction, patients did not feel 'better', and found it difficult to let go of worries and fears around OAB. These findings suggest that a person with OAB may need support even after a 'successful' treatment, as OAB continues to be at the centre of patients' lives.